Invented Writing Activities in Nordic Early Childhood Education and Care – Traces of Didactics in Practice - Sofie Tjäru; Randi Høyland; Hilde Hofslundsengen; Maria Magnusson (Nordic Journal of Literacy Research)
This study investigates early childhood education and care (ECEC) teachers’ reported practices and views regarding children’s invented writing. A total of 222 teachers from Finland, Norway, and Sweden responded to a questionnaire on their practices regarding invented writing activities and rated statements on a Likert scale. The data were analyzed quantitatively with descriptive statistics, and open answers were analyzed qualitatively using content analysis. The results showed that few teachers arranged daily writing activities and that writing was especially uncommon with children aged three years and younger. A dominant view expressed was that children needed to be of a certain age for writing to be relevant and that the children were simply too young. The writing that did take place focused on letters and children’s names. Although most teachers reported that the alphabet was visibly displayed in their ECEC units, few teachers had included writing materials in play settings. However, some teachers reported physical and social learning environments that engaged children in invented writing. We believe that the latter teachers’ accounts indicate a didactic approach in Nordic ECEC that could serve as a starting point for future investigations regarding the didactics of invented writing in ECEC.